2021
DOI: 10.3390/s21082826
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Artificial Neural Network Equalizer in Optical Camera Communications

Abstract: In this paper, we propose and validate an artificial neural network-based equalizer for the constant power 4-level pulse amplitude modulation in an optical camera communications system. We introduce new terminology to measure the quality of the communications link in terms of the number of row pixels per symbol Npps, which allows a fair comparison considering the progress made in the development of the current image sensors in terms of the frame rates and the resolutions of each frame. Using the proposed equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Next, this information is transmitted toward the vehicles behind, which are not able to detect the danger, using the taillights as a VLC transmitter. The following vehicle uses a camera system to receive this information using the concept of Optical Camera Communication (OCC) [ 55 , 56 ]. Although the working principle is remarkable, the system has several disadvantages generated by the limitations associated with OCC.…”
Section: Discussion About the Importance Of This Work Differences Fro...mentioning
confidence: 99%
“…Next, this information is transmitted toward the vehicles behind, which are not able to detect the danger, using the taillights as a VLC transmitter. The following vehicle uses a camera system to receive this information using the concept of Optical Camera Communication (OCC) [ 55 , 56 ]. Although the working principle is remarkable, the system has several disadvantages generated by the limitations associated with OCC.…”
Section: Discussion About the Importance Of This Work Differences Fro...mentioning
confidence: 99%
“…The introduction of NN equalizer has impact significant improvement of visible light communication system [12]. Although it is in an early stage, some articles shows tremendous achievement but lack of computational complexity [13] and very poor generation. In [14], authors have used NN for data decoding considering motion by waving their hand.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, in VLC links, the artificial neural network (ANN) architectures have been attached very attention from many researchers. The existing works in the literature related to ANN‐based VLC systems focused on expanding the rate of communication 26 . On the other hand, the linear and nonlinear distortions have emerged as major difficulties to high‐speed VLC links 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The existing works in the literature related to ANN-based VLC systems focused on expanding the rate of communication. 26 On the other hand, the linear and nonlinear distortions have emerged as major difficulties to high-speed VLC links. 27 In Reference 28, it was reported that a 170 Mb/s OOK-VLC system eliminates the ISI by employing an ANN-based equalizer.…”
Section: Introductionmentioning
confidence: 99%